Effects of enzymatic treatments on yuzu (Citrus junos) juice residue under low temperature by adding small amounts of enzyme solutions on paste yields, and their volatile compositions - Osaka, Takashi; Sakai, Chikako; Fujii, Kazuyoshi (Food Science and Technology Research, 2023)
This study investigated the effects of enzymatic treatments on yuzu (Citrus junos) squeezed juice residue under low temperature by adding small amounts of enzyme solutions on paste yields, and their volatile compositions. Yuzu juice residue was enzymatically degraded by adding different volumes of enzyme solutions to residue to obtain paste. The yield of paste was 68.1% in the treatment of adding equal amounts of enzyme solutions to residue for 5h at 40 °C. In the treatments of adding 10 % or 5 % (v/w, based on the weights of the wet residue) volume of enzyme solution to residue for 24h at 10 °C, yields of paste were 67.6 % or 67.1 % (dry matter base), respectively. In enzymatic treatments of adding 10 % or 5 % (v/w, based on the weights of the wet residue) volume of enzyme solutions to residue at 10 °C, pastes were obtained without the processes of heating and separating the water. Degraded residue was strained with a spatula by hand to obtain paste in those treatments, because it was not necessary to separate the water from the mixture due to the small amount of enzyme solution that was added. Relative percentages of the volatile components of α-pinene, σ-elemene, decanal, β-elemene, and γ-cadinene were higher in the paste enzymatically treated at 10 °C than in the paste treated at 40 °C.